Analysis of the need for e-comic development of light and optics material based on problem-based learning for students' learning styles - Rizki Dwika Septiarini; Atika Anggraini (Universitas Muhammadiyah Mataram, 2026)
Education in the 21st century requires integration with digital technology to create engaging learning experiences aligned with students’ learning styles. However, students often experience difficulties in understanding light and optics due to conventional teaching methods and limited learning media. This study aims to analyze the need for developing problem-based learning (PBL)-based e-comics on light and optics materials that suit students’ learning styles. This research used a descriptive qualitative approach involving 32 students of class 8B at MTsN 6 Kediri and one science teacher. Data were collected through questionnaires to identify learning styles and interviews to examine learning difficulties and teaching practices. Data analysis was conducted using descriptive analysis of questionnaire and interview results.The results showed that students had difficulty understanding light and optics because learning was still conventional, physics was considered difficult, and media were not varied. Questionnaire results indicated that students tended to have visual learning styles. E-comics are appropriate as they present material through contextual visual stories and interactive elements, and can be integrated with PBL to support problem-solving and conceptual understanding. The findings indicate a strong need to develop PBL-based e-comics as an innovative learning medium that supports visual learning styles and improves students’ understanding.